2019
DOI: 10.3390/s19071734
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-Based In-Situ Detection and Quantification of Delamination in Composite Plates

Abstract: This paper presents a new methodology for detecting and quantifying delamination in composite plates based on the high-frequency local vibration under the excitation of piezoelectric wafer active sensors. Finite-element-method-based numerical simulations and experimental measurements were performed to quantify the size, shape, and depth of the delaminations. Two composite plates with purpose-built delaminations of different sizes and depths were analyzed. In the experiments, ultrasonic C-scan was applied to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 53 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Also, it was found that the transverse position of the delamination has a greater effect on the damping parameter (tanδ). Mei et al [32] also found that the different sizes and transverse position of delamination within a carbon fiber-reinforced polymer (CFRP) composite significantly modified the local defect resonance frequency based on a vibration in-situ detection method. They found strong local vibrations only occurred in the delamination regions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was found that the transverse position of the delamination has a greater effect on the damping parameter (tanδ). Mei et al [32] also found that the different sizes and transverse position of delamination within a carbon fiber-reinforced polymer (CFRP) composite significantly modified the local defect resonance frequency based on a vibration in-situ detection method. They found strong local vibrations only occurred in the delamination regions.…”
Section: Discussionmentioning
confidence: 99%
“…The detection and characterization of various types of composite damage are quite difficult. Delamination is a common and dangerous failure mode for composite structures, because it occurs and grows in the absence of any visible surface damage, making it difficult to detect through visual inspection [2]. In addition, barely visible impact damage (BVID) due to low-velocity impact, in the form of fiber breakage, matrix cracking, and interlaminar delamination, is also invisible to the naked eye and is easily induced from various sources such as bird strikes, tools dropped on parts, or runway debris [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [24] proposed that the variations of modal frequency under mass loading could be used to quantify the effects of delamination in laminated composites. Mei et al [25] studied high-frequency local vibration for detecting and quantifying the size, shape, and depth of delamination in composite plates. Sikdar et al [26] investigated the effects of debonding and variable ambient temperature on the propagation of Lamb wave in composite materials.…”
Section: Introductionmentioning
confidence: 99%